Recent political disturbances in Nepal threaten rhinos: lessons to be learned - Esmond Martin; Chryssee Martin; Lucy Vigne (Pachyderm)
This article describes rhino poaching in Nepal during the Maoist insurgency and the social unrest that took place from 2000 to late 2007, with special emphasis on the latter two years. There are three areas in Nepal with rhinos: Chitwan and Bardia National Parks and Suklaphanta Wildlife Reserve. In 2006 there were at least 21 rhinos poached in Nepal, a continuing trend of serious poaching since 2001. In 2007, poaching fell; officials recorded only five rhinos known to have been poached, although in reality the figure was higher. That year the country returned to relative peace and many of the guard posts were re-instated. New approaches to rhino conservation in Nepal are needed now, including those that have proved to be successful elsewhere in Asia and Africa, in order to better safeguard Nepal’s rhinos once more. The rhinos are particularly vulnerable when they wander outside the protected areas. Recommendations are given, such as consideration for some rhinos to be managed in temporary sanctuaries, both governmental and private. The recent political unrest has been a warning that in such conditions a country can be destabilized very quickly with government and Army attention shifted away from wildlife conservation. Rhinos in these circumstances are easy targets to poachers. Thus, more involvement of the private sector in rhino protection is vital.